2019
DOI: 10.1101/757146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the effects of alcohol and tobacco use on cardiovascular disease using multivariable Mendelian randomization

Abstract: Alcohol and tobacco use, two major modifiable risk factors for cardiovascular disease (CVD), are often consumed together. Using large publicly available genome-wide association studies (results from > 940,000 participants), we conducted two-sample multivariable Mendelian randomization (MR) to simultaneously assess the independent effects of alcohol and tobacco use on CVD risk factors and events. We found genetic instruments associated with increased alcohol use, controlling for tobacco use, associated with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
2
0
0
Order By: Relevance
“…Many of the results that we found elaborate the lipid profiles of lipoprotein subclasses in more detail than the previous studies. Our results regarding the effects of alcohol on IDL and large LDL-related lipids conflicted with some observational studies’ findings ( Würtz et al, 2016 ; Du et al, 2020 ), but agreed with another MR-study ( Rosoff et al, 2019 ), whereas in our study we showed that the same relationships hold for each of the alcohol subgroups as well. Our finding of vegetarianism raising 18:2 linoleic acid replicated a previous finding from a randomized trial conducted on subjects with T2D ( Kahleova et al, 2013 ), whereas our results show that this finding applies for the general population in a larger sample as well.…”
Section: Discussionsupporting
confidence: 86%
“…Many of the results that we found elaborate the lipid profiles of lipoprotein subclasses in more detail than the previous studies. Our results regarding the effects of alcohol on IDL and large LDL-related lipids conflicted with some observational studies’ findings ( Würtz et al, 2016 ; Du et al, 2020 ), but agreed with another MR-study ( Rosoff et al, 2019 ), whereas in our study we showed that the same relationships hold for each of the alcohol subgroups as well. Our finding of vegetarianism raising 18:2 linoleic acid replicated a previous finding from a randomized trial conducted on subjects with T2D ( Kahleova et al, 2013 ), whereas our results show that this finding applies for the general population in a larger sample as well.…”
Section: Discussionsupporting
confidence: 86%
“…As we have seen, the more powerful ALDH2 variant, which also allows stratification to exclude bias due to pleiotropy or LD-clearly demonstrates an effect of alcohol on HDL-C [51,53]. Furthermore, using multiple variants in largely European-origin populations with a sample of ~ 1M, a clear effect of alcohol on HDL-C is seen, which is robust to stringent interrogation with sensitivity analyses [82]. As HDL-C does not influence CVD risk [31,32] any failure of ADH1B to recapitulate the effects of alcohol on HDL-C will not distort the estimates of alcohol on cardiovascular outcomes.…”
Section: Pleiotropysupporting
confidence: 54%